Kepemimpinan Tranformasional dan Komitmen Organisasional: Pemberdayaan sebagai Variabel Mediasi - Muhdiyanto, - (Universitas Muhammadiyah Semarang, 2011)
This aim of this research is to test the transformasional leadership and organizational commitment as mediatingempowerment. There are several hypotheses to be tested in this research. (1) There is effect transformasionalleadership on organizational commitment. (2) Empowerment for effect mediating transformasional leadershipon organizational commitment. Data for this study were collected using a questionnaire survey sent to 120responden in financial institute non bank at Magelang religion and participated in this research, also same 87%response rate. The study employs a moderated regression analysis (MRA) to analyze the hypotheses and assit bySPSS 16.00 from windows programs. The result supported all of hypotheses of study.